Epidural lipomatosis with cauda equina syndrome in chronic alcoholic patient: A case report - Kim, Sung-Soo (Int J Surg Case Rep, 2017)
INTRODUCTION: Epidural lipomatosis of the lumbar spine is a rare condition, which is described as the accumulation of fat in the extradural territory. PRESENTATION OF CASE: We report the case of a 60-year-old, non-obese, and chronic alcoholic man who was transferred to our spine department with cauda equina syndrome (CES) for 4 months. On magnetic resonance imaging (MRI), spinal epidural lipomatosis (SEL) was confirmed in the multilevel lumbar lesion. A decompression surgery was performed and the patient recovered significantly. DISCUSSION: The patient was not obese, had no abnormal liver laboratory test results, and no history of steroid injection or administration. The clinical signs at onset suggested bilateral lower cauda equina dysfunction, indicating a more diffuse involvement, consistent with lumbosacral epidural lipomatosis. CONCLUSION: This case report is the first description of SEL in a non-obese, chronic alcoholic patient who was neither receiving steroids nor had any kind of endocrinopathy.